2015
DOI: 10.1007/s00294-015-0549-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic inference and SSR characterization of tropical woody bamboos tribe Bambuseae (Poaceae: Bambusoideae) based on complete plastid genome sequences

Abstract: The complete plastome sequencing is an efficient option for increasing phylogenetic resolution and evolutionary studies, as well as may greatly facilitate the use of plastid DNA markers in plant population genetic studies. Merostachys and Guadua stand out as the most common and the highest potential utilization bamboos indigenous of Brazil. Here, we sequenced the complete plastome sequences of the Brazilian Guadua chacoensis and Merostachys sp. to perform full plastome phylogeny and characterize the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
4
10
2
Order By: Relevance
“…Penta-and hexanucleotide cpSSRs were observed only in E. baxteri and E. diversicolor, respectively (Table 2), all in non-coding regions. Similar to the results presented herein, penta-and hexanucleotide repeats occurred at a low frequency in Bambuseae species, but in coding sequences (Vieira et al 2015). For cpDNA of R. piresii, Vieira et al (2016a) found no penta-or hexanucleotide cpSSRs, which is consistent with the results found for most of the studied Eucalyptus species.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Penta-and hexanucleotide cpSSRs were observed only in E. baxteri and E. diversicolor, respectively (Table 2), all in non-coding regions. Similar to the results presented herein, penta-and hexanucleotide repeats occurred at a low frequency in Bambuseae species, but in coding sequences (Vieira et al 2015). For cpDNA of R. piresii, Vieira et al (2016a) found no penta-or hexanucleotide cpSSRs, which is consistent with the results found for most of the studied Eucalyptus species.…”
Section: Resultssupporting
confidence: 90%
“…Currently there are no other studies that assess the distribution and organization of cpSSRs in Eucalyptus species;; therefore, we provide a general comparison between our results and published studies on other plant species. For example, Vieira et al (2015) analyzed the occurrence, type, and distribution of cpSSRs for 20 Bambuseae species and their results showed an average total of 141.8 cpSSRs, with a predominance of mono-and dinucleotide repeats. Similarly, Vieira et al (2016a), studying Retrophyllum piresii Silba C.N.…”
Section: Resultsmentioning
confidence: 99%
“…The neotropical woody bamboo clade includes subtribes Chusqueinae, Arthrostylidiinae and Guaduinae. Placement of Chusqueinae (Chusquea) sister to a maximally supported cladecomprising Arthrostylidiinae and Guaduinae is congruent with other studies(Sungkaew et al, 2009;Kelchner, 2013;Chokthaweepanich, 2014;Vieira et al, 2016;Zhang et al, 2016c). Within Guaduinae, Olmeca reflexa and Otatea acuminata are strongly supported sister taxa in most trees, but in tree R, Olmeca reflexa and Guadua weberbaueri form a moderately supported clade.…”
supporting
confidence: 88%
“… Saarela et al (2015) summarized all publications of grass plastomes published as of September 2014, and many new plastomes have since become available. Recent grass plastome sequences have been variously published in short contributions ( Myszczyński et al, 2015 ; Wang & Gao, 2015 , 2016 ; Lu et al, 2016 ; Perumal et al, 2016 ) or in the context of detailed phylogenomic analyses of different grass lineages, including the PACMAD clade ( Cotton et al, 2015 ; Teisher et al, 2017 ), Bambusoideae ( Wu et al, 2015 ; Wysocki et al, 2015 ; Attigala et al, 2016 ; Vieira et al, 2016 ; Zhang & Chen, 2016 ), Aristidoideae ( Besnard et al, 2014 ), Brachypodieae ( Sancho et al, 2017 ), early diverging grasses ( Burke et al, 2016a ), Panicoideae ( Burke et al, 2016b ), Chloridoideae ( Duvall et al, 2016 ), Zea ( Orton et al, 2017 ), Micrairoideae ( Duvall et al, 2017 ), Pooideae ( Saarela et al, 2015 ) and Oryzeae ( Kim et al, 2015 ; Liu et al, 2016 ; Wu & Ge, 2016 ; Zhang et al, 2016a , 2016b ). Phylogenomic analyses of plastomes have contributed increased resolution and support for many relationships within and among grass subfamilies compared with earlier single- and multi-gene plastid studies.…”
Section: Introductionmentioning
confidence: 99%